Electrocautery Verses Scalpel for Abdominal Incisions in Repeat Caesarian Section (Medical Forum Monthly, 2021)
Objective: To compare the mean operative time, post-operative pain and blood loss with electrocautery verses scalpel in repeat caesarian sections for abdominal incisions.Study Design: Randomized controlled trial studyPlace and Duration of Study: This study was conducted at the MCH Centre PIMS Hospital, Islamabad from June, 2020 to December, 2020 for a period of six months.Materials and Methods: Total 100 women with singleton pregnancy (assessed on USG) of gestational age 37-41 weeks (assessed by LMP) undergoing cesarean section of 18-45 years of age were selected and randomly divided into two groups of 50 women in each. Women with Gestational Diabetes, Primigravida, hepatic or renal impairment were excluded. Group A included woman who had incision with electrocautery. Group B included women who had incision with scalpel. All operations in both groups were done by same surgeon and operative time, post-operative pain and blood loss was measured.Results: In our study, the mean operative time in Group A (Electrocautery group) was 66.92 ± 7.39 minutes while in Group B (scalpel group) was 86.98 ± 5.84 minutes (p-value = 0.0001). Mean blood loss in Group A (Electrocautery group) was 194.32 ± 56.01 ml while in Group B (scalpel group) was 418.96 ± 26.18 ml (p-value = 0.0001). Mean post-operative pain in Group A (Electrocautery group) was 1.84 ± 1.13 while in Group B (scalpel group) was 3.28 ± 1.37 (p-value = 0.0001).Conclusion: This study concluded that the electrocautery incision is better than scalpel skin incisions in terms of incision time, blood loss and post-operative pain.